Analytical solutions of equation for the order parameter of dense superfluid neutron matter with anisotropic spin-triplet p-wave pairing at finite temperatures - Tarasov, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The previously derived equations for the components of the order parameter (OP) of dense superfluid neutron matter (SNM) with anisotropic spin-triplet p-wave pairing and with taking into account the effects of magnetic field and finite temperatures are reduced to the single equation for the one-component OP in the limit of zero magnetic field. Here this equation is solved analytically for arbitrary parametrization of the effective Skyrme interaction in neutron matter and as the main results the energy gap (in the energy spectrum of neutrons in SNM) is obtained as nonlinear function of temperature T and density n in two limiting cases: for low temperatures near T = 0 and in the vicinity of phase transition temperature Tc0(n) for dense neutron matter from normal to superfluid state. These solutions for the energy gap are specified for generalized BSk21 and BSk24 parametrizations of the Skyrme forces (with additional terms dependent on density n) and figures are plotted on the interval 0.1n0 < n <2.0n0, where n0 = 0.17 fm–3 is nuclear density.